Provincial Administration and Local Nobility in Courland in the Middle of the 19th Century - N. A. Mogilevskii (Vestnik MGIMO-Universiteta)
In the article, on the example of the conflict of the Courland governor P.A. Valuev with the Baltic nobility, happened in 1857, the legal status of the Baltic nobility in the Russian Empire is considered. The main issue considered in the work is the problem of the relationship between the imperial center and the national outskirts in the middle of the 19th century, which, in turn, is closely related to the results of the Northern War (1700-1721), which ended for Russia with a victory over Sweden and the annexation of the former part of the Swedish kingdom Estonia and Livonia. The local aristocracy received guarantees from the highest Russian authorities to preserve all privileges, which put it in a slightly different position than the nobility of the inner Russian provinces. Under Catherine II, when Courland was incorporated into Russia, these privileges were extended to the Courland barons. In the XIX century, under Nicholas I and Alexander II, all the "rights and liberties" of the Baltic nobles were also invariably confirmed. As a result, there was a situation in which the German barons considered themselves bound by personal obligations personally with the Russian monarch. This situation, typical of medieval feudal Europe, ran counter to the Russian patrimonial socio-political model, which irritated the Russian elite. The special position of the Courland nobility eventually led to a clash with the governor P.A. Valuev, who, acting within the framework of general imperial legislation, tried to establish general imperial orders in the province. Governor-General of the Baltic Region A.A. Suvorov, Interior Minister S.S. Lanskoy and Emperor Alexander II himself were involved in the clash. And although Valuev's position ultimately triumphed, and his opponent, Baron Gan, was forced to leave the post of Courland leader of the nobility, in general, this did not change the situation in any way. The model of “center-outskirts” relations considered in the article allows a deeper analysis of the difficulties that the local administration in the Baltic region faced when trying to unify the local administration system with the general imperial one. The main conclusion of the article can be considered the thesis that the Russian central government, represented by the governor and the governor-general, did not dare to drastically break the existing management model, in which the local elite (nobility) had a significant impact on the situation in the region. Courland, along with other Baltic provinces, remained a special territory in the political and legal landscape of the Russian Empire.